Strategi Kampanye Paket Victory-Joss melalui Media Online dalam Kontestasi Pilgub Nusa Tenggara Timur 2018-2023 - Yudia Agustin Telnoni; Yermia Dj. Manafe; Silvania S. E. Mandaru (Universitas Nusa Cendana, 2019)
Campaign strategies are needed by each regional head candidate who participated in the contestation of governor election, including the Victory-Joss who participated in the contestation of the 2018 East Nusa Tenggara governor election. Victory-Joss who previously were not very well-known by East Nusa Tenggara communities must strive to reach all areas of East Nusa Tenggara, which are an archipelago province, to be able to introduce themselves, bring political messages to almost all people of East Nusa Tenggara so that they can be acknowledged more closely, and all their best intentions for East Nusa Tenggara can be recognized. This is where an extension of Victory-Joss’s campaign team, which is the online media, as one of the Victory-Joss’s package campaign strategies is needed to reach wider communities. The purposes of this study are to discover and explain the Victory-Joss’s package campaign strategy and the reasons for conducting the campaign strategy by the Victory-Joss pair to gain East Nusa Tenggara communities’ supports in the 2018 East Nusa Tenggara regional election. The research type that was employed was qualitative historical research with a case study method. Data in this study were collected through interviews and document collection techniques. The results showed that the campaign strategy through online media conducted by the Victory-Joss package was to form a media team consisting of five online media that have existed in East Nusa Tenggara, namely seputar-ntt.com, likuraionline.com, savanaparadise.com, nttsatu.com, and mediantt.com, and also to form an IT team and social media teams to distribute videos and memes related to Victory-Joss’s package’s words when campaigning on the field as well as in the Victory-Joss’s package campaign contained in the five online media’s publicity that contained news about the appearance of Victory-Joss’s package in traditional and cultural events which were held in the midst of the East Nusa Tenggara communities.